Modern method of treatment of compression fracture of the spine with stabilization with a metal corrector - Marat Rabandyarov; Ardak Nurmukhanov; Azat Satzhanov (National Scientific Medical Center, 2017)
A clinical example of the treatment of a pediatric patient with a compression fracture in the lumbar spine. The child was operated on the L1 compression fracture, a course of conservative treatment with postoperative immobilization in a soft corset.